Pelatihan pembelajaran efektif berbasis TSAC bagi Guru sekolah dasar di Jawa Tengah - Utomo, Arief Cahyo; Rosyadi, Ajib; Sejati, Amelia Wahyu; Candradewi, Frida Fembriani; Affandi, Muhammad Rasyid; Hidayat, Muhamad Taufik; Muhroji, Muhroji (Nur Science Institute, 2021)
The purpose of this community service is to provide an effective teaching training based on TSAC (Teaching Skill Assessment Checklists) for elementary school teachers in Central Java. The strategic and appropriate target audience involved in this activity were elementary school teachers in Central Java as many as 20 person (Surakarta, Klaten, Karanganyar, Demak, Sragen, Brebes). The service materials are as follows: (1) Creating a supportive and warm classroom climate (2) Using waiting time during questions (3) Arranging content for effective presentations (4) Assessing, commenting, and discussing homework (5) Multitasking. A question and answer session was held and a discussion on the problems encountered in the field. After that, to determine the success of the implementation of this activity, an evaluation is carried out at the end of the implementation of the activity. The results of the implementation showed that the participants were very enthusiastic in participating the training. From the results of the question and answer, there are also many problems that exist in the elementary school in Central Java.